2018
DOI: 10.1177/0268580918762059
|View full text |Cite
|
Sign up to set email alerts
|

Global institutions and local filtering: Introducing independent directors to Taiwanese corporate boards

Abstract: Drawing on the idea of selective interaction between organizations and environments, the authors examine how organizations change their traditional practices when they are exposed to new institutional environments. In the context of corporate governance change in response to financial market globalization, they argue that global institutional influence is moderated by local corporate control contexts that function as filtering mechanisms. The authors empirically analyse the adoption of a new corporate governan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Yet such partner-mediated uncertainty reduction is likely to be moderated by contextual factors related to transfer of information from the environment and its processing by firms. Prior literature has shown that external influences on firms are filtered through firms' local context that includes a wide range of factors, such as ownership and control structures (e.g., Chung and Kim, 2018), regulatory landscape (e.g., Sanders and Tuschke, 2007), decision-making processes (e.g., Kennedy and Fiss, 2009), embeddedness in exchange relationships (e.g., Ahmadjian and Robbins, 2005) , managerial predispositions (e.g., Fiss and Zajac, 2004), and firms' experience (e.g., Dimov and Martin de Holan, 2010) embeddedness in their environment and the processing of external information in order to attain a workable level of certainty, new market choice can be seen as a process in which firms obtain information about potential market opportunities through their links to the environment and process it in the course of new market selection. Factors pertaining to firms' embeddedness in the networks that transfer information about new markets and those that affect how firms process obtained information are, thus, likely to affect the extent of partners' influence on firms' new market choice.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet such partner-mediated uncertainty reduction is likely to be moderated by contextual factors related to transfer of information from the environment and its processing by firms. Prior literature has shown that external influences on firms are filtered through firms' local context that includes a wide range of factors, such as ownership and control structures (e.g., Chung and Kim, 2018), regulatory landscape (e.g., Sanders and Tuschke, 2007), decision-making processes (e.g., Kennedy and Fiss, 2009), embeddedness in exchange relationships (e.g., Ahmadjian and Robbins, 2005) , managerial predispositions (e.g., Fiss and Zajac, 2004), and firms' experience (e.g., Dimov and Martin de Holan, 2010) embeddedness in their environment and the processing of external information in order to attain a workable level of certainty, new market choice can be seen as a process in which firms obtain information about potential market opportunities through their links to the environment and process it in the course of new market selection. Factors pertaining to firms' embeddedness in the networks that transfer information about new markets and those that affect how firms process obtained information are, thus, likely to affect the extent of partners' influence on firms' new market choice.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Market entry is a complex process (Zachary et al, ) that is influenced by a variety of factors that may interact with, complement or substitute for one another in affecting new market entry. While prior studies on external influences on firms indicates that such influences are filtered by firms’ local context (e.g., Chung and Kim, ; Kennedy and Fiss, ; Sanders and Tuschke, ), with the exception of Tuschke et al () the nascent literature on network effects in market entry says little about the conditions under which network ties can be expected to have greater or lesser impact on firms’ choice of new markets. To build a nuanced and differentiated understanding of the role of interfirm ties in new market choice it is necessary to delineate factors that facilitate, moderate, or impede network effects.…”
Section: Introductionmentioning
confidence: 99%